the Pajuro (erythrina edulis) endangered andean food - Escamilo Cárdenas, Simón (2012)
This work deals with the study of a leafy tree called bean or pajuro measuring 12 to 15 m. height; provides human few large grains dark brown measuring between 4 and 5 cm, which are within a sheath of 20 to 30 cms. long, quite similar to pacay. Limited number of Andean peasants living in the departments of Huanuco, Ancash, La Libertad, Cajamarca and Amazonas, are regular consumers pajuro. In all other departments, during our journey in search of this plant, we have found only faint traces and evidence of their former presence, now no longer sow the locals do not know, is extinct. For its high starch content (33%) in 100 grams of fresh material can be prepared both savory and sweet dishes. It has a high quality protein of 25% (per 100 grams of seeds) is eaten in soups, salads, stews, porridges, breads, cookies, beverages such as milk and pajuro chicha. The pajuro as tree supports prolonged droughts, requires no fertilizer, nitrogen is provided, controls soil erosion, is semicultivado, no plant care required. Today, there are fewer plants, is in the process of extinction.